KARAKTERISTIK PENDERITA HIV/AIDS YANG BEROBAT JALAN DI RSUD Dr. PIRNGADI MEDAN TAHUN 2015 - renta purba; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT HIV/AIDS is one of the health problems that threaten many countries around the world. Acquired Immunodeficiency Syndrome (AIDS) is a collection symptoms caused of the decreasing of the immune systems. According to the Indonesian Ministry of Health, the number of  HIV/AIDS cases were reported during in 2015 that as many as 30,935 cases of HIV and AIDS 6,081. This study is descriptive by using case series design. The sample population was all patients with HIV / AIDS 109 cases. The data analysis uses a secondary data by using Chi-square and Fisher 's ExactThe results of this research showed the highest  proportion of patients with HIV / AIDS outpatient at the age 30-39 years old is male ( 34.8 % ) , Batak (49.6%), High School (67.8%), self-employed (42.1%), married (46.7%), area in Medan (84.4%), heterosexual (64.3%), have opportunistic infections (70.6%), pulmonary tuberculosis/gland (61.0%), last count of CD4 200-499 µl (47, 1%), stage 1 line ARV therapy (64.9%). There are no significant differences between the sexes with the transmission risk factors (p=0.098), the work with the transmission risk factors (p=0.725), marital status with the transmission risk factors (p = 0.188), age with the opportunistic infections (p = 0.522), gender with the opportunistic infections (p=0.817) and there is a significant difference between the education with the  transmission risk factors (p=0.026).It is expected for people to abstain from sex before marriage, no promiscuity, especially productive age keep away from drugs and  tattoos. For Dr. Pirngadi Hospital Medan especially the VCT department  emphasizes the understanding of patients on ARV therapy, more active in social support and the patients/families counseling program also increase the completeness of patients status card. Keywords : HIV/AIDS, Characteristic, Dr. Pirngadi Hospital Medan